DFT Computational Design of a Ligand‐Driven Light‐Induced Mechanism for Spin‐State Switching. Issue 24 (1st July 2013) - Starikova, Alyona A.; Minyaev, Ruslan M.; Starikov, Andrey G.; Minkin, Vladimir I.
Abstract: A new ligand‐driven light‐induced spin‐state switching mechanism has been designed based on B3LYP*/6‐311++G(d, p) DFT calculations of a series of Co II, Ni II, and Cu II complexes with photochromic 2 H ‐chromene (2 H ‐1‐benzopyran) ligands4 –8 functionalized with N donor groups. The photoinduced electrocyclic rearrangements of the bis‐chelate four‐coordinate Ni II complexes with the ring‐closed forms of the ligands, all with high‐spin ground electronic states, are predicted to lead to the formation of a mixture of approximately equal amounts of the diamagnetic square‐planar and paramagnetic pseudo ‐tetrahedral isomers of these complexes containing ring‐opened o ‐quinonoid forms of the ligands. Of the Co II complexes, only that with the 2 H ‐chromen‐8‐amine ligand4 exhibits the properties required for manifestation of the photoinitiated spin‐state switching. No local minima corresponding to four‐coordinate copper complexes with ring‐closed isomers of the functionalized 2 H ‐chromenes were located on the respective potential energy surfaces. In their ring‐closed forms, 2 H ‐chromenes react with Cu II ions to give two‐coordinate Cu I complexes, whereas ring‐opened o ‐quinonoid isomers form four‐coordinate bis‐chelate Cu II complexes. In the Ni II complexes with isomeric forms of 2 H ‐pyrano[3, 2‐ h ]quinoline ligand8, the counterions Cl – and even BF4 – enter into the coordination sphere of the central atom to form stable six‐coordinate metal complexes with high‐spin ground states. The predicted capacity of the Ni II complexes for light‐induced spin‐state switching is retained with the bulkier BPh4 – counterion. The low‐spin state of the ion‐pair formed by the complex with the ring‐opened form of ligand8 is 10.5 kcal mol –1 more energetically favorable than the high‐spin form. Abstract : B3LYP*/6‐311++G(d, p) DFT calculations have been performed on a series of bis‐chelate four‐coordinate Co II, Ni II, and Cu II complexes of photochromic 2 H ‐cromene ligands. In the case of the Ni II complexes, the light‐driven electrocyclic rearrangements of the ligand moieties lead to sharp switching of the spin states of the complexes.